Artificial intelligence and the future of evaluation education: Possibilities and prototypes - Tilton, Zach; LaVelle, John M.; Ford, Tian; Montenegro, Maria (New Directions for Evaluation, 2023)
Advancements in Artificial Intelligence (AI) signal a paradigmatic shift with the potential for transforming many various aspects of society, including evaluation education, with implications for subsequent evaluation practice. This article explores the potential implications of AI for evaluator and evaluation education. Specifically, the article discusses key issues in evaluation education including equitable language access to evaluation education, navigating program, social science, and evaluation theory, understanding evaluation theorists and their philosophies, and case studies and simulations. The paper then considers how chatbots might address these issues, and documents efforts to prototype chatbots for three use cases in evaluation education, including a guidance counselor, teaching assistant, and mentor chatbot for young and emerging evaluations or anyone who wants to use it. The paper concludes with ruminations on additional research and activities on evaluation education topics such as how to best integrate evaluation literacy training into existing programs, making strategic linkages for practitioners, and evaluation educators.